The role of mineral-related industries in Chinese industrial pattern. (June 2022) - Li, Weidong; Wang, Anjian; Zhong, Weiqiong; Xing, Wanli; Liu, Jinna
Abstract: Mining industry provides raw materials for economic development, and is a basic industry with strong correlation with other industries. Meanwhile, mining industry possess the feature of "high energy consumption, high pollution and high emissions". Especially in today's society where environmental protection is increasingly becoming the main theme, it has become an important issue for people to actively coordinate the relationship between mining and environmental protection, and promote the green transformation of mining industry. Combining industrial relationship and complex network, industrial complex network is applied to explore the industrial relevance, which is a perfect method to research industrial pattern. Based on the input-output data of China (1990–2018), this paper constructed the industrial complex network model to describe the evolution characteristics of Chinese industrial pattern. Then we focused on the mineral-related industries, to explore their role and position in Chinese industrial pattern by analysis of network overall and individual indicators and community division. The results show that Chinese industrial network has small world property, and the closeness of various industries is increasing, and the characteristic of industrial clusters ais obvious; The system of Chinese manufacturing industry is becoming more and more perfect and remains an important pillar and foundation of the national economy; Smelting and processing of metals industry plays an important role in connecting the preceding and the following. This paper provides a new perspective for the study of China's mining industry pattern and puts forward corresponding policy suggestions for the adjustment of industrial structure. At the same time, relevant development experience can also serve as a reference for subsequent countries. Highlights: The industrial complex network in China (1990–2018) has small world property. The important role of the tertiary industry is strengthening. The industrial system of Chinese manufacturing industry is becoming more and more perfect. The position of the industry - Smelting and Processing of Metals is crucial, which exerts important mediating effect.